Atomically resolved FeSe/SrTiO3(001) interface structure by scanning transmission electron microscopy. (30th March 2016) - Li, Fangsen; Zhang, Qinghua; Tang, Chenjia; Liu, Chong; Shi, Jinan; Nie, CaiNa; Zhou, Guanyu; Li, Zheng; Zhang, Wenhao; Song, Can-Li; He, Ke; Ji, Shuaihua; et al.
Abstract: Interface-enhanced high-temperature superconductivity in one unit-cell FeSe films on SrTiO3 (001) (STO) substrate has recently attracted much attention in condensed matter physics and material science. By combined in situ scanning tunneling microscopy/spectroscopy and ex situ scanning transmission electron microscopy studies, we report on atomically resolved structure including both lattice constants and actual atomic positions of the FeSe/STO interface under both non-superconducting and superconducting states. We observed TiO2 double layers and significant atomic displacements in the top two layers of STO, lattice compression of the Se–Fe–Se triple layer, and relative shift between bottom Se and topmost Ti atoms. By imaging the interface structures under various superconducting states, we unveil a close correlation between interface structure and superconductivity. Our atomic-scale identification of FeSe/STO interface structure provides insight on investigating the pairing mechanism of this interface-enhanced high-temperature superconducting system.